Comparison of 1L Adjuvant Auxiliary Preparations with 2L Solely Polyethylene Glycol plus Ascorbic Acid Regime for Bowel Cleaning: A Meta-analysis of Randomized, Controlled Trials. (19th February 2021) - Yuan, Xin; Zhang, Zhixin; Xie, Jiarong; Zhang, Yu; Xu, Lu; Wang, Weihong; Xu, Lei
Abstract : The effectiveness of additional usage of adjuvants for bowel preparation is still unclear. This study compared 1L polyethylene glycol plus ascorbic acid with adjuvant drug regimens (1L PEG-AA, lower volume) with 2L polyethylene glycol plus ascorbic acid (2L PEG-A, low volume) to evaluate whether the adjuvants can be used to reduce the standard dosage of purgative further. The PubMed/MEDLINE, EMBASE, Cochrane Library, and Web of Science database were searched for randomized controlled trials (RCTs). The primary outcome was the efficacy of bowel preparation, and the secondary outcomes were patients' tolerability and complication rate. The overall quality of evidence was assessed using the GRADEpro guideline development tool. Five RCTs with a total of 1013 patients from Korea were included. The majority of patients were outpatients from different hospitals. The pooled data showed no significant difference in the adequate bowel preparation rate (89.3% versus 89.4%, RR 1, 95% CI 0.95-1.05, I 2 = 47 % ) as well as in the complication rate (RR for nausea 1.22, 95% CI 0.89-1.65, I 2 = 49 % ; RR for bloating 0.96, 95% CI 0.73-1.28, I 2 = 0 % ; RR for vomiting 0.69, 95% CI 0.32-1.50, I 2 = 33 % ; RR for abdominal pain 1.01, 95% CI 0.61-1.69, I 2 = 0 % ). But a significantly higher willingness rate was observed in the lower volume (85.1% versus 67.9%, RR 1.25, 95% CI 1.14-1.38, I 2 = 46 % ). The quality of primary outcome evidence was moderate. The findings of this meta-analysis revealed that 1L PEG-AA may be a viable alternative to 2L PEG-A, with comparable effectiveness, better patient preference, and no statistically significant adverse event occurrence.